PARCIJALNE KVANTITATIVNE PROMJENE ANTROPOLOŠKIH KARAKTERISTIKA STUDENTICA POD UTICAJEM FITNESS PROGRAMA THAI-BO - Muris Đug; Branimir Mikić; Jasmin Mehinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The main goal of this research is determing levels of tranformation process of morphological characteristics, motoric and funkcional abilities of female students under influence of 6- months fitness program Thai-bo. Tha sample for this research consists of 64 female students age 19-21 of Tuzla University. Results of this research show us that fitness programm Thai-bo, afther 6-months of programming workout, on sample of 64 female students, produced statisticly significant partial quantative changes in tested anthropological characteristics.